The Effect of Atmosphere, Price Perception and Service Quality on Customer Satisfaction Kaizen Heritage - Matwes, Gavin; Siahaan, Sinthon Levi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research seeks to assess the effects of atmosphere, price perception, and service quality on customer satisfaction at Kaizen Heritage Café in Bekasi. A quantitative research design was employed through the dissemination of questionnaires to 133 customers, the study utilized accidental sampling, while SmartPLS 3.0 was applied to analyze the measurement and structural models. The results demonstrate that all three independent variables significantly and positively affect customer satisfaction. Among them, service quality exhibits the highest impact, followed by atmosphere and price perception. Collectively, these variables explain a considerable amount of the variability in customer satisfaction. Findings highlight the importance for café operators to consistently enhance the physical environment, ensure fair pricing strategies, and deliver exceptional service quality to achieve and sustain customer satisfaction. This study provides theoretical contributions to the field of service marketing and practical insights for improving business performance in the café industry.